Applied Multiregional Demography: Migration and Population Redistribution - Rogers, Andrei. author. aut Link
XV, 114 p. 24 illus.
Keywords: This book shows the effectiveness of multiregional demography for studying the spatial dynamics of migration and population redistribution. It examines important questions in demographic analysis and shows how the techniques of multiregional analysis can lead to answers that sometimes contradict conventional wisdom. The book reconsiders conclusions reached in the literature regarding several fundamental common sense demographic questions in migration and population redistribution, including: Are the proximate sources of urban population growth mostly due to migration or natural increase? Is it mostly migration or “aging-in-place” that has been driving Florida’s elderly population growth? Do the elderly return “home” after retirement more than the non-elderly do? Are the migration and settlement patterns of the foreign-born different from those of the native-born? Do simple population projection models outperform complex ones? Does longer life lead to longer ill-health? For each demographic question it reconsiders, the book illustrates how an inappropriate specification can bias findings to favor a possibly incorrect conclusion. It shows how a multiregional analysis can better illuminate the dynamics that underlie the observed population totals and lead to a more informed conclusion. Offering insights into the effectiveness of multiregional demography, this book serves as a valuable resource for students and researchers searching for a better way to answer questions in demographic analysis and population dynamics. .